Phenotypic and molecular characterization of IMP-producing Enterobacterales in Spain: Predominance of IMP-8 in Klebsiella pneumoniae and IMP-22 in Enterobacter roggenkampii - Cañada-García, Javier E.; Grippo, Natalin; de Arellano, Eva Ramírez; Bautista, Verónica; Lara, Noelia; Navarro, Ana María; Cabezas, Teresa; Martínez-Ramírez, Nora Mariela; García-Cobos, Silvia; Calvo, Jorge; Cercenado, Emilia; Aracil, Belén; et al. (Frontiers in Microbiology, 2022)
Objectives: Little is known about IMP-producing Enterobacterales (IMP-Ent) in Europe. We analyzed molecular epidemiology and microbiological features of IMP-Ent isolates (Spain 2012-2021). Materials and methods: IMP-Ent isolates submitted to our reference laboratory were included. Antibiotic susceptibility was performed using microdilution method (EUCAST), and IMP-carbapenemase activity was measured with carbapenemase inhibitors, the β-CARBA method, the modiﬁed Hodge test (MHT), and the modified carbapenemase inhibition method (mCIM). All isolates collected were sequenced for high-resolution single-nucleotide polymorphism (SNP) typing, core genome multilocus sequence typing (cgMLST), and resistome analysis. Results: Fifty IMP-Ent isolates, collected from 20 hospitals in 13 Spanish provinces, were detected: Klebsiella pneumoniae (IMP-Kpn) (24; 48%), Enterobacter cloacae complex (IMP ECC) (22; 44%), Klebsiella oxytoca (two; 4%), Serratia marcescens (one; 2%) and Escherichia coli (one; 2%). All isolates were positive by the MHT and β-CARBA tests; 48 (96%) were mCIM positive; 11 (22%) and 26 (52%) displayed positive inhibition with dipicolinic (meropenem) and EDTA (ertapenem), respectively. Five IMP-carbapenemase types were identified: IMP-8 (22; 44%), IMP-22 (16; 32%), IMP-13 (8; 16%), IMP-28 (two; 4%), and IMP-15 (two; 4%), predominating IMP-8 in K. pneumoniae and IMP-22 in the E. cloacae complex. IMP-13 was exclusively identified in K. oxytoca and IMP-15 in E. cloacae complex. Predominant STs were ST405 (29.2%), ST15 (25%) and ST464 (20.8%) in IMP-Kpn and ST96 (59%) and ST182 (22.7%) in IMP-ECC. Colistin and amikacin were the most active non-carbapenem antibiotics against IMP-Ent. Conclusions: IMP-Ent isolates remain infrequent in Spain, although in recent years have been circulating causing nosocomial outbreaks, being IMP 8 producing K. pneumoniae and IMP 22-producing E. cloacae complex the most frequently detected in this study. Inhibition with EDTA or dipicolinic acid presented false negative results in some IMP-producing strains. Active microbiological and molecular surveillance is essential for a better comprehension and control of IMP-Ent dissemination.